Protection Systems for Reinforced Concrete with Corrosion Inhibitors - Zacharopoulou, Angeliki; Zacharopoulou, Eugenia; Batis, George (Scientific Research, 2014)
This paper examines the use of corrosion inhibitors in order to protect the reinforcement of concrete. For this purpose mortar specimens were constructed with or without corrosion inhibitors and were partially immersed in sodium chloride. Corrosion inhibitors were used as admixture into concrete and were sprayed on the external surface of mortar specimens. In all mortar specimens, electric junction between reinforcements was achieved. The methods that were used for the evaluation of the reinforcement corrosion in concrete, included half-cell potential measurements, polarization curves of reinforced rebars and mass loss of the reinforcement. Finally, the durability of concrete after the use of corrosion inhibitors was also examined.
Keywords: Reinforced; Corrosion Inhibitors; Corrosion Protection